Extensive erythema elevatum diutinum associated with IgA monoclonal gammopathy: a rare case report - Rijhwani, Manish; Yadav, Divya; Nijhawan, Manisha; Verma, Arvind (International Journal of Research in Dermatology, 2021)
Erythema elevatum diutinum (EED) is a rare form of leukocytoclastic vasculitis with an unclear pathogenesis. Almost 250 cases of EED have been reported in the literature, associated with several diseases and presented with various clinical features. Term 'diutinum' means chronic, describes one of the main characteristic features. The duration is very long, varying between one to more than 39 years. We report a rare presentation of EED in a 58-years-old man who presented with extensive and symmetrical, persistent, erythematous to violaceous plaques over trunk and limbs and popular-nodular lesions present over pinna and dorsum of hands with burning sensation and itching over few lesions, in association with IgA monoclonal gammopathy.